PERAN PERENCANAAN PAJAK DAN LABA SEBELUM PAJAK TERHADAP PEMBAYARAN PAJAK (STUDI PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2020-2021) - Rulyna Sabathini Tesalonica; Judith Tagal Gallena Sinaga (Jurnal Ekonomis, 2023)
This study was conducted to confirm the role of tax planning and profit before tax for banking company tax payments during the two years of research, to forty-two companies with a total of eight-four which used purposive sampling in their collection method. Researchers used descriptive anaylysis method with multiple linear regression. The results show tax planning has an effect on tax payments, profit before tax has a positive effect on tax payments; simultaneously tax planning and profit before tax effect on tax payments.